2019
DOI: 10.1016/j.rmed.2019.105803
|View full text |Cite
|
Sign up to set email alerts
|

Real-life comparison of pirfenidone and nintedanib in patients with idiopathic pulmonary fibrosis: A 24-month assessment

Abstract: Background: Real-life data on the use of pirfenidone and nintedanib to treat patients with idiopathic pulmonary fibrosis (IPF) are still scarce. Methods: We compared the efficacy of either pirfenidone (n=78) or nintedanib (n=28) delivered over a 24-month period in patients with IPF, followed at two regional clinic centers in Italy, with a group of patients who refused the treatment (n=36), and who were considered to be controls. All patients completed regular visits at 1-to 3-month intervals, where primary [fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 25 publications
5
42
1
Order By: Relevance
“…Although our data may be influenced by demographic discrepancies between the two groups, our results suggest that the two drugs have substantially the same performance in preventing functional deterioration and reducing mortality. These assumptions are in line with a recent paper by Cerri et al (2019) , although our study considered a larger cohort of patients (including those with advanced disease) and a much longer follow-up, further underlining the reliability of both antifibrotic drugs in the treatment of IPF.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although our data may be influenced by demographic discrepancies between the two groups, our results suggest that the two drugs have substantially the same performance in preventing functional deterioration and reducing mortality. These assumptions are in line with a recent paper by Cerri et al (2019) , although our study considered a larger cohort of patients (including those with advanced disease) and a much longer follow-up, further underlining the reliability of both antifibrotic drugs in the treatment of IPF.…”
Section: Discussionsupporting
confidence: 86%
“…A metanalysis published in 2016 failed to find any significant differences in safety or concerning progression between the two drugs, whereas nintedanib appeared to be more effective in reducing acute exacerbations and mortality risk ( Rogliani et al, 2016 ). Two other retrospective observational studies confirmed the substantial similarity of the two antifibrotic drugs in terms of effectiveness and tolerability, albeit with a relatively short follow-up ( Bargagli et al, 2019 ; Cerri et al, 2019 ).…”
Section: Introductionmentioning
confidence: 76%
“…Previous studies have shown that nintedanib and pirfenidone have a similar effect on lung function decline. Furthermore, no significant differences in all-cause mortality and frequency of side-effects were found between the two drugs [2,3,5,21]. However, these studies did not compare patient experiences and satisfaction between both antifibrotic drugs.…”
Section: Discussionmentioning
confidence: 94%
“…These drugs slow down disease progression, may reduce the rate of acute exacerbations, and seem to prolong survival [ 2 4 ]. The decision to prescribe either nintedanib or pirfenidone is usually based on the specific side-effect profiles, comorbidities, co-medication, and a patient’s preferences [ 5 , 6 ]. The prevalence of adverse events has been reported in randomized controlled trials and registries with real-world data.…”
Section: Introductionmentioning
confidence: 99%
“…IPF cannot be cured at present. The purpose of treatment is to delay disease progress, improve quality of life and prolong survival (Cerri et al, 2019). IPF has poor prognosis, median survival time after diagnosis is about 2 to 3 years.…”
Section: Discussionmentioning
confidence: 99%